Ivan Goncharov’s Novel “A Common Story” and the Problem of “Petersburg Text” - Belyaeva, Irina; Senilova, Alexandra (Slavica, 2021)
The article raises the question about the nature of the “Petersburg text” in the novel “A Common Story”, about its correlation with the general body of the “Petersburg text” of Russian literature and about its individual meanings in Goncharov’s prose. Various levels of the “Petersburg text” are considered: the expression of the category of the “inner state” of the hero, as well as culture and nature. It is concluded that Goncharov’s novel does not fully fit into the mainstream of the “Petersburg text” of Russian literature, but adopts the basic principles of its construction, and also has great potential for the semantic increments of the individual local Petersburg dictionary, which is determined by Goncharov’s irony and symbolization.